(untitled) (Mantichora. Italian Journal of Performance Studies, 2024)
This paper examines, through the sampling and analysis of some key scenes, the very recent series on PRIME entitled Swarm. It is the second authorial attempt by Donald Glover, aka Childish Gambino, after Atlanta. The main serial product investigated offers an opportunity to frame the delicate function of the auteur-producer, according to Mittell’s insights, and to reason, even from an intradiegetic point of view, about an unforeseen horizon of manifestation of fandom. Tied to this discourse is a reasoning, by analogy, with the entomological sphere that Glover’s intuition repeatedly invokes.